Variability in the sensitivity of Phytophthora capsici isolates to potassium phosphonate - Y.R. SARMA, S.S. VEENA, M. ANANDARAJ* (Indian Phytopathology, 2010)
Potassium phosphonate is recommended for the control of Phytophthora foot rot disease of black pepper (Piper nigrum L.). Sensitivity of 29 isolates of Phytophthora capsici, obtained from black pepper plants at various locations of Kerala and Karnataka, to potassium phosphonate was studied. There were significant variations EC50 and EC90 values for mycelial growth, sporulation, zoospore release and zoospore germination to different concentrations of potassium phosphonate. The EC50 values for mycelial growth, sporulation, zoospore release and zoospore germination ranged from 89.3µg/ml-603µg/ml, 0.25µg/ml- 36.3 µg/ml, 0.84 µg/ml to 29.9 µg/ml and 1.5 µg/ml-37.3 µg/ml, respectively. The EC90 values for mycelial growth were 573.5 µg/ml to 1635.20 µg/ml, for sporulation it was 2.1 µg/ml to 129.3 µg/ml, for zoospore release it was 14.2µg/ml to 72.7 µg/ ml and for zoospore germination it was 5.6 µg/ml to 103.4 µg/ml. Among the four stages of life cycle of P. capsici, sporulation stage was the most sensitive to potassium phosphonate and mycelial growth was the least affected. Sporulation being an important event in the spread of epidemics, application of potassium phosphonate at critical time would be essential in preventing the spread of infection.